Analisis dan Perancangan Feature Engineering Pada SQL Execution Plan Aplikasi Apache Spark - dariato, eri (Institut Agama Islam Negeri (IAIN) Curup, 2021)
To process data in RDBMS, it is commonly used what is called SQL. This SQL can be simple or complex depending on the join statement, the tables involved, filter statement, and many more. If it is complex and burdensome to the system, then the performance of the database as a whole will decrease and SQL execution will not finish. That's why it's important to know, what components are involved when executing SQL through the SQL Execution Plan. The components in the SQL Execution Plan can be very diverse, so artificial intelligence is used to help analyze and conclude what factors have the most role in determining performance. Furthermore, these factors are called feature engineering. The purpose of this research is to formulate what features exist in the SQL Execution Plan when we send SQL commands to the system. The research method used is the Prototyping process model.